2001
DOI: 10.1093/bja/87.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus: a review of the literature

Abstract: Under anaerobic conditions found in necrotic or infected tissue, the tetanus bacillus secretes two toxins: tetanospas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
338
2
56

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(405 citation statements)
references
References 91 publications
9
338
2
56
Order By: Relevance
“…Set against this clinical picture in the prodromal stadium, patients in developing countries are more likely to present with progressed and unambiguous symptoms i.e. severe spasms of the facial musculature (risus sardonicus) and opisthotonus [2]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Set against this clinical picture in the prodromal stadium, patients in developing countries are more likely to present with progressed and unambiguous symptoms i.e. severe spasms of the facial musculature (risus sardonicus) and opisthotonus [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Although these cases are usually associated with good outcome, rare cases with involvement of the cranial nerves (cephalic tetanus) have a high risk of progressing to generalized tetanus with a high mortality [2]. In tetanus neonatorum, the early symptoms include suckling and feeding problems, vomiting and seizures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, malaria reduces placental transfer of antibodies to the fetus. 8 Even in developed countries, such as the United States and the United Kingdom, serological surveys have shown that 49-66% of people over 60 years of age have inadequate immunity. Indeed, 70% of tetanus cases and 80% of deaths in these countries occur in people over 50 years of age.…”
Section: Pathophysiologymentioning
confidence: 99%